2013
DOI: 10.1007/s13204-013-0235-8
|View full text |Cite
|
Sign up to set email alerts
|

Numerical solution of non-Newtonian nanofluid flow over a stretching sheet

Abstract: The steady flow of a Jeffrey fluid model in the presence of nano particles is studied. Similarity transformation is used to convert the governing partial differential equations to a set of coupled nonlinear ordinary differential equations which are solved numerically. Behavior of emerging parameters is presented graphically and discussed for velocity, temperature and nanoparticles fraction. Variation of the reduced Nusselt and Sherwood number against physical parameters is presented graphically. It was found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
63
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(65 citation statements)
references
References 19 publications
(16 reference statements)
2
63
0
Order By: Relevance
“…The governing partial differential equations are first transformed into a system of ordinary differential equations before being solved numerically. The results are then compared with those obtained by Khan and Pop 6 and Nadeem et al 16 for some particular cases of the present study, to support their validity. This problem is relevant to several practical applications in the field of metallurgy, chemical engineering, etc.…”
Section: Introductionsupporting
confidence: 80%
See 1 more Smart Citation
“…The governing partial differential equations are first transformed into a system of ordinary differential equations before being solved numerically. The results are then compared with those obtained by Khan and Pop 6 and Nadeem et al 16 for some particular cases of the present study, to support their validity. This problem is relevant to several practical applications in the field of metallurgy, chemical engineering, etc.…”
Section: Introductionsupporting
confidence: 80%
“…In this paper, we present an analysis which may be regarded as an extension of the work of Nadeem et al 16 by considering the effects of MHD and heat generation or absorption. The governing partial differential equations are first transformed into a system of ordinary differential equations before being solved numerically.…”
Section: Introductionmentioning
confidence: 99%
“…He also depicted the collaborative effects of temperature-dependent viscosity. A few recent studies exploring the the characteristics of nanofluids may be found in [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…In the recent years, boundary layer flow of non-Newtonian fluids over a stretching surface has received special attention from the researchers (Ellahi et al 2012;Nadeem et al, 2014;Bose et al, 2015;Akbar et al, 2016;Sahoo, 2010). This is because of their advanced industrial, engineering science and technological applications such as glass fibber, wire drawing, paper production, extrusion of plastic sheet, hot rolling, drawing of plastic films and many others.…”
Section: Introductionmentioning
confidence: 99%